Lower reflectivity and higher minority carrier lifetime of hand-tailored porous silicon - 张楠生 马忠权 周呈悦 何波 (Journal of semiconductors, 2009)
Solar cell grade crystalline silicon with very low reflectivity has been obtained by electrochemically selective erosion.The porous silicon（PS） structure with a mixture of nano-and micro-crystals shows good antireflection properties on the surface layer, which has potential for application in commercial silicon photovoltaic devices after optimization.The morphology and reflectivity of the PS layers are easily modulated by controlling the electrochemical formation conditions（i.e., the current density and the anodization time）.It has been shown that much a lower reflectivity of approximately 1.42% in the range 380-1100 nm is realized by using optimized conditions.In addition, the minority carrier lifetime of the PS after removing the phosphorus silicon layer is measured to be ～3.19 μs.These values are very close to the reflectivity and the minority carrier lifetime of Si3N4 as a passivation layer on a bulk silicon-based solar cell（0.33% and 3.03 μs, respectively）.